KEKUATAN HUKUM PERKAWINAN ADAT DI DESA HILITOTAÖ KECAMATAN AMANDRAYA KABUPATEN NIAS SELATAN DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Agape Laia (Jurnal Panah Hukum, 2024)
In essence, marriage is an important legal event for everyone, because it not only gives rise to rights and obligations, but is also able to provide legal implications for various aspects of existing life demands. In an effort to meet the demands of these interests, marriages are often carried out based on a traditional legal system that has been around for a long time and is believed to be a rule that is able to accommodate various community interests, such as the traditional marriage system in Hilitotaö Village, Amandraya District, South Nias Regency. The problem is: what is the legal strength of a customary marriage in the perspective of Law Number 1 of 1974 concerning Marriage? To provide an answer to the problem in question, the author uses a type of sociological (empirical) legal research guided by primary data obtained through observation, interviews and document study. In conducting interviews with respondents, the author determined the sample by grouping respondents (stratified random sample) consisting of traditional elders (satua mbanua), elements of the local government (village heads and BPD). Based on the results of research conducted, it was discovered that the traditional marriage system in Hilitotaö Village, Amandraya District, South Nias Regency, has been going on for quite a long time, and has become an important instrument in measuring whether a marriage is valid or not. This means that marriages that are not performed according to custom are considered by the local community to be invalid according to custom, as a consequence they can be ostracized from the social environment of society. In relation to the conditions for the validity of a marriage according to Law Number 1 of 1974 concerning Marriage, this is not something that is in dispute, in fact the conditions for the validity of a marriage according to Law Number 1 of 1974 concerning Marriage are a complement to the existing traditional marriage system. This means that the legal force of customary marriage becomes more perfect if the marriage is carried out in accordance with the provisions of Law Number 1 of 1974 concerning Marriage.